(untitled) (Russian Medical and Social Journal, 2019)
Extraosseous manifestations are found in less than 5% of patients with multiple myeloma. Involvement of the gastrointestinal system in the course of multiple myeloma (MM) is extremely rare. Imaging is required for correct staging, in the followup after treatment and is predictor of prognosis. Several imaging technologies are used for the diagnosis and management of patients with MM. Conventional radiography, computed tomography (CT), magnetic resonance imaging (MRI) and nuclear medicine imaging - positron emission tomography (PET) combined with CT (PET/CT) and PET combined with MRI (PET/MRI) are all used in clarifying the extent of bone and soft tissue lesions in MM. The brief literature review on extramedullary lesions in MM and their imaging with recommendations is given. We describe the imaging in diagnostics and management of an rare case of secondary extramedullary plasmacytoma (EMP) in relapse involving the pancreas and duodenum with the bleeding in a patient with MM, IgA lambda, stage II, after 6-years treatment with chemotherapy, autologous peripheral blood stem cell transplantation and radiotherapy. EMP was detected by PET/CT before the appearance of obvious clinical signs, and then EMP was monitoring by PET/CT, X-ray and ultrasound.